Salvadora persica: Nature's Gift for Periodontal Health - Mohamed Mekhemar; Mathias Geib; Manoj Kumar; Radha; Yasmine Hassan; Christof Dörfer (MDPI AG, 2021)
Salvadora persica (SP) extract, displays very valuable biotherapeutic capacities such as antimicrobial, antioxidant, antiparasitic and anti-inflammatory effects. Numerous investigations have studied the pharmacologic actions of SP in oral disease therapies but its promising outcomes in periodontal health and treatment are not yet entirely described. The current study has been planned to analyze the reported effects of SP as a support to periodontal therapy to indorse regeneration and healing. In consort with clinical trials, in vitro investigations show the advantageous outcomes of SP adjunctive to periodontal treatment. Yet, comprehensive supplementary preclinical and clinical investigations at molecular and cellular levels are indispensable to reveal the exact therapeutic mechanisms of SP and its elements for periodontal health and therapy.